Derivatization of Inseparable Ursolic and Oleanolic Acids of Fagraea fragrans Fruits to Enhance Their Anticancer Activity - Dasril Basir; Miksusanti Miksusanti; Susilawati Susilawati (Universitas Jenderal Soedirman, 2022)
Inseparable Ursolic acid and its isomeric oleanolic acid are the major compounds in Fagraea fragrans fruits. The white solid crystals , 3.1 % of these triterpenic acids are easyly isolated from alcoholic extracts of these dried fruits. They are well known in both cosmeticeutical and medicinal industries. Therefore the objective of this work is to derivative those to be the inseparable ethyl ursolate 3-ethyl ether [its isomeric ethyl oleanolate 3-ethyl ether], and to evaluate their anticancer activity against P-388 murine leukemia cells. The results are 71% of the derivatives have been successfully made from the inseparable ursolic [its isomeric oleanolic] acids by in situ reaction between those triterpenic acids with thionyl chloride and ethanol in benzene. The anticancer activity of ethyl ursolate 3-ethyl ether [its isomeric ethyl oleanolate 3-ethyl ether] against P-388 murine leukemia cells with IC50 value of 31.36 µg/mL is twofold (1.7) more potent then their mother compounds, the inseparable ursolic [its isomeric oleanolic] acids with IC50 value of 53.5 µg/mL.